(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the influence of information technology misuse and student integrity on academic dishonesty among Accounting Education students at Surabaya State University. This study used a quantitative approach with a causal associative design. The study population consisted of 215 Accounting Education students from Surabaya State University, class of 2023, with a sample of 140 students selected using a simple random sampling technique. The research data were collected using a questionnaire with a Likert scale that measured the variables of information technology misuse, student integrity, and academic dishonesty. Data analysis was carried out through several stages, namely instrument validity and reliability testing, classical assumption testing, and multiple linear regression analysis to examine the partial and simultaneous effects between research variables. The results showed that information technology misuse had a positive and significant effect on academic dishonesty, while student integrity had a negative and significant effect on academic dishonesty. Simultaneously, information technology misuse and student integrity had a significant effect on academic dishonesty behavior. These findings indicate that improving student integrity and controlling the use of information technology are important aspects in efforts to reduce academic dishonesty behavior.